Antibacterial Activities of Sirih Merah (Piper crocatum) Leaf Extracts - Puspa Julistia Puspita; Mega Safithri; Nirmala Peni Sugiharti (IPB University, 2018)
Piper crocatum is one of medicinal herbal plants with a large number of benefits. Usually herbal plants have activity as antibacterial agent. Therefore, the objectives of this research were to obtain information on antibacterial activities of the leaf extracts of Piper crocatum againts four types of bacteria, in that Staphylococcus, Bacillus substilis, Escherichia coli, and Pseudomonas aeruginosa and then to analyze the phytochemistry of the leaf extracts of Piper crocatum. The leaves of Piper crocatum were extracted by maceration and reflux using ethanol 30%. The assays of the antibacterial activities and phytochemistry on the extracts were carried out using the method of Maria Bintang. Results showed that the yield of the extraction using ethanol by maceration method was 20.8%. Meanwhile, using the reflux method, the yield was obtained about 26.25%. The phytochemistry analysis showed that the leaf extracts of Piper crocatum contained alkaloid, steroid and tanin. According to this study, it was found that the leaf extract of Piper crocatum can be used to inhibit the growth of B. subtilis and P. aeuruginosa, but can not inhibit the growth of E.coli and S. aureus.